2016
DOI: 10.11113/jt.v78.10146
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Estimation for a Mechanistic Model of High Dose Irradiation Damage Using Nelder-Mead Simplex Method and Genetic Algorithm

Abstract: Radiation therapy is one of the cancer cells treatments that use high-energy radiation to shrink tumors and kill cancer cells. Radiation therapy kills cancer cells by damaging their DNA directly or creates charged particles within the cells that can in turn damage the DNA. As a side effect of the treatment, the radiation therapy can also damage the normal cell that located at parts of our body. The main goals of radiation therapy are to maximize the damaging of tumors cell and minimize the damage of normal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The result on the elasticity analysis of the model illustrates that the major control response to the survival fraction of non-targeted cells is regulated by the DSBs induction coefficient among bystander cells, ϑ and successful repair probability of nontargeted cells, p. For further development, the mathematical model developed in this work should be continued with parameter fitting procedure. Parameter fitting procedure is a method which requires an experimental data in order to prove the accuracy of a mathematical model [37]. It also can be suggested that the bystander factors concentration released by the targeted cells into the medium follow a saturating Michaelis-Menten saturating function so that, the possible value of maximum signal concentration released could be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The result on the elasticity analysis of the model illustrates that the major control response to the survival fraction of non-targeted cells is regulated by the DSBs induction coefficient among bystander cells, ϑ and successful repair probability of nontargeted cells, p. For further development, the mathematical model developed in this work should be continued with parameter fitting procedure. Parameter fitting procedure is a method which requires an experimental data in order to prove the accuracy of a mathematical model [37]. It also can be suggested that the bystander factors concentration released by the targeted cells into the medium follow a saturating Michaelis-Menten saturating function so that, the possible value of maximum signal concentration released could be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In [7] used NMS optimization in estimating the value of parameters in the case of high dose effects of irradiation on the targeted cells. Then in [10] showed that NMS optimization is much superior to the Genetic Algorithm in inding the least SEE between the model simulation data and the experimental data. In [11] studied the distance to the Galactic cen-ter determined by G, K, and M stars.…”
Section: Introductionmentioning
confidence: 99%